SUMBANGAN SPIRITUALITAS SANTO VINSENSIUS A PAULO BAGI PELAYANAN KATEKIS DI PAROKI TAMIANG LAYANG - Ngarani, Nullya; Adinuhgra, Silvester (SEPAKAT-Jurnal Pastoral Kateketik, 2016)
Catechists in carrying out their missionary tasks have never escaped the challenges. Sometimes with the various obstacles that come make them desperate, disappointed and even slowly leave their mission duties. This fact is occurring in the Parish of St. Mikael Tamiang Layang, the diocese of Palangkaraya. Based on the data we obtained, it was found that the Catechists had various challenges in their duties. These challenges are quite disturbing their service. Nonetheless, the Spirituality of Saint Vincent de Paul has motivated them to remain steadfast and faithful to their vocation as the preacher of the word.